A microscopic analysis of the effects of root surface scaling with different power parameters of er,cr: YSGG laser - Oliveira, Guilherme José Pimentel Lopes de [UNESP]; Cominotte, Mariana Aline [UNESP]; Beraldo, Tamara Pádua Pereira [UNESP]; Sampaio, Jose Eduardo Cezar [UNESP]; Marcantonio, Rosemary Adriana Chiérici [UNESP] (Wiley, 2015)
The aim of this study was to evaluate the effects of different power parameters of an Erbium, Cromium: Yttrium, Scandium, Gallium, Garnet laser (Er,Cr:YSGG laser) on the morphology, attachment of blood components (ABC), roughness, and wear on irradiated root surfaces. Sixty-five incisive bovine teeth were used in this study, 35 of which were used for the analysis of root surface morphology and ABC. The remaining 30 teeth were used for roughness and root wear analysis. The samples were randomly allocated into seven groups: G1: Er,Cr:YSGG laser, 0.5 W; G2: Er,Cr:YSGG laser, 1.0 W; G3: Er,Cr:YSGG laser, 1.5 W; G4: Er,Cr:YSGG laser, 2.0 W; G5: Er,Cr:YSGG laser, 2.5 W; G6: Er,Cr:YSGG laser, 3.0 W; G7: scaling and root planning (SRP) with manual curettes. The root surfaces irradiated by Er,Cr:YSGG at 1.0 W and scaling with manual curettes presented the highest degrees of ABC. The samples irradiated by the Er,Cr:YSGG laser were rougher than the samples treated by the manual curette, and increasing the laser power parameters caused more root wear and greater roughness on the root surface. The Er,Cr:YSGG laser is safe to use for periodontal treatment, but it is not appropriate to use irradiation greater than 1.0 W for this purpose. Microsc. Res. Tech. 78:529–535, 2015. © 2015 Wiley Periodicals, Inc.
Keywords: Healing; Hight intensive laser; Periodontitis; Root roughness; Root wear